Improving Learning Outcomes of Globalization Subthemes Around Me through Power Point Media in Class VI SDN 238 Palembang - Sari, Imelda (PPSDP International Journal of Education, 2024)
In this study, the problem raised by the researcher was, “Can the use of power point media improve learning outcomes for the sub-theme of globalization around me in class VI at SDN 238 Palembang?” This research aims to improve the learning outcomes of class VI PPKn students at SDN 238 Palembang by using power point media. This research was carried out in class VI at SDN 238 Palembang. The research method used is classroom action research, with two cycles carried out, namely cycle 1 and cycle 2. This was done to determine improvements in student learning outcomes. From the results of data analysis for each cycle, the following results were obtained: the percentage of achievement of learning completeness, which was originally in cycle 1, was affective 60%, psychomotor 53%, and cognitive 60%, then increased in cycle 2 to 93%. Affective, 93% Psychomotor, and 100% Cognitive, or an increase of 33% Affective, 40% Psychomotor, and 40% Cognitive. By looking at the results between cycles 1 and 2, there was an increase in learning outcomes after using power point learning media. From these results, it can be said that learning using power point media can improve student learning outcomes.